2011
DOI: 10.1590/s0034-71672011000500004
|View full text |Cite
|
Sign up to set email alerts
|

Atenção humanizada ao parto de adolescentes: análise das práticas desenvolvidas em um centro obstétrico

Abstract: RESUMOEstudo quantitativo que objetivou analisar as práticas desenvolvidas na assistência à adolescente, a partir do relato dos trabalhadores de um Centro Obstétrico de um Hospital Universitário, com base na proposta de humanização do parto do Ministério da Saúde. Segundo os trabalhadores, estão sendo desenvolvidas práticas úteis na assistência ao parto, dentre as quais as orientações sobre formas de relaxamento no trabalho de parto, o incentivo ao vínculo entre mãe e fi lho e a amamentação. Porém, o direito a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
22

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 15 publications
1
3
0
22
Order By: Relevance
“…Similar to the speech of a teenager puerperal who had no opinion on the procedure and showed certain compliance with the situation, the literature points out that, although the majority of adolescents included in the study have had a considerable number of prenatal consultations, many times the young women do not express any opinion on the episiotomy because they are not even informed about the procedure. 23 Such situation was also demonstrated in this study, in which some adolescents have shown discontentment with the procedure and with the attitude of the professional, but not questioned.…”
Section: Discussionsupporting
confidence: 70%
“…Similar to the speech of a teenager puerperal who had no opinion on the procedure and showed certain compliance with the situation, the literature points out that, although the majority of adolescents included in the study have had a considerable number of prenatal consultations, many times the young women do not express any opinion on the episiotomy because they are not even informed about the procedure. 23 Such situation was also demonstrated in this study, in which some adolescents have shown discontentment with the procedure and with the attitude of the professional, but not questioned.…”
Section: Discussionsupporting
confidence: 70%
“…15 Therefore, the respectful approach directed to these women and the effective communication established contributed to a satisfactory relationship with the professionals, to create a link between motherhood and the user, and consequently to the perception of welcome and care for pregnant women.…”
Section: ] " (Denise)mentioning
confidence: 99%
“…contato precoce e do aleitamento materno, por ser um procedimento intervencionista (MATOS et al, 2010;NAGAHAMA;SANTIAGO, 2011;SVENSSON et al, 2013 A assistência humanizada prestada à parturiente/puérpera e ao recém-nascido requer cuidados assistenciais que vão além do processo biológico, pois conforme descrito nas falas dos participantes do presente estudo, as mulheres trazem consigo mitos, tabus, questões culturais, sociais e econômicas que podem interferir na assistência. Daí a necessidade de os profissionais de saúde estarem adaptados às transformações da sociedade, respeitando os reais valores, a cultura e os saberes resultantes da experiência humana, e a construção de um espaço de socialização no que tange às parturientes assistidas (BUSANELLO et al, 2011;SANTOS et al, 2013).…”
Section: A Concepção E a Prática Do Contato Precoce Pelos Profissionaunclassified
“…. Assim, a estrutura adequada do CO é um requisito fundamental, a fim de que a assistência prestada à parturiente/puérpera seja humanizada para a integridade da mulher, proporcionando um ambiente acolhedor, calmo, com iluminação adequada, apoio, segurança e tranquilidade para essa mulher e seu filho recém-nascido (BRASIL, 2008b;BUSANELLO et al, 2011).…”
Section: "Porque Chega Ali a Primeira Coisa A Paciente Tá Com Dor; Counclassified
See 1 more Smart Citation